2009
DOI: 10.1007/s10549-009-0344-y
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative genes dominate malignancy-risk gene signature in histologically-normal breast tissue

Abstract: PURPOSE-Historical data have indicated the potential for the histologically-normal breast to harbor pre-malignant changes at the molecular level. We postulated that a histologically-normal tissue with "tumor-like" gene expression pattern might harbor substantial risk for future cancer development. Genes associated with these high-risk tissues were considered to be "malignancy-risk genes".EXPERIMENTAL DESIGN-From a total of 90 breast cancer patients, we collected a set of 143 histologically-normal breast tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
138
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(146 citation statements)
references
References 35 publications
6
138
2
Order By: Relevance
“…Investigations of gene expression in HN breast epithelium are limited (Finak et al, 2006;Grigoriadis et al, 2006;Tripathi et al, 2008;Chen et al, 2009). Our results contrast with one study that did not find a different gene expression between morphologically normal epithelium microdissected from RM and HN samples (Finak et al, 2006).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Investigations of gene expression in HN breast epithelium are limited (Finak et al, 2006;Grigoriadis et al, 2006;Tripathi et al, 2008;Chen et al, 2009). Our results contrast with one study that did not find a different gene expression between morphologically normal epithelium microdissected from RM and HN samples (Finak et al, 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…Another study (Chen et al, 2009) found a proliferative gene expression signature in morphologically benign tissue (not necessarily HN) of patients with invasive carcinoma, but no controls were reported. Third, evaluation of the RM -HN gene list leads to several speculations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 238 of our own samples (datasets Frankfurt, Frankfurt-2, and Frankfurt-3) which have been described previously (Ahr et al 2002 [9], [10], Rody et al 2008 [11], Ruckhäberle et al 2008 [12], and Rody et al 2007 [13], respectively) as well as 2792 samples from 22 different publicly available datasets (Table 1): Rotterdam [14][15][16], Mainz [17], Trans-BIG [18], Oxford-Untreated [19], London [20], London-2 [21], Oxford-Tamoxifen, Veridex-Tam [22], Stockholm [23], Uppsala [24,25], San Francisco [26], New York [27], MDA133 [28], EORTC [29], Edinburgh [30], ExpO [31], Signapore [32], Genentech [33], Boston [34], Berlin [35], Paris [36], and Tampa [37]. For comparability, only the ProbeSets from the Affymetrix HG-U133A microarray were used from seven datasets where HG-U133?…”
Section: Methodsmentioning
confidence: 99%